Crossing the Line Violence, Play, and Drama in Naval Equator Traditions - Bronner, Simon J. (Meertens Ethnology Cahiers, 2006)
For centuries, new sailors from European and North American countries have embraced often brutal hazing in an elaborate ceremony at sea called 'crossing the line' (British-American) and 'Neptunusfeest' (Dutch). Typically enacted upon crossing the equator, the beatings, dunks, sexual play, mock baptisms, mythological dramas, crude shavings and haircuts, and drinking and swallowing displays have attracted a number of protests and even bans as well as staunch defenses and fond reminiscences. The custom has especially drawn criticism since the late twentieth century with the integration of women into the military and the questioning of its hierarchical codes of manliness. In this study, the persistent ceremony's changing meaning into the twenty-first century is examined with considerations of development, structure, symbolism, performance, and function. A timely study revising previous assumptions about the custom's origins, diffusion, and functions.